Racial discrimination in Latin American school settings: evidence from Brazilian adolescents - Kezauyn Miranda Aiquoc; Maria do Socorro da Silva; Alessandra Aparecida da Silva Menezes; Mercês de Fátima dos Santos Silva; Talita Araujo de Souza; Isabelle Ribeiro Barbosa (Global Health Promotion, 2026)
This study evaluated the prevalence and factors associated with perceived racial discrimination among Brazilian schoolchildren. A cross-sectional study used data from Sample 1 of the 2015 National School Health Survey. The prevalence of perceived racial discrimination and its association with individual, socioeconomic, health and school factors were analyzed using prevalence ratios (PR) with 95% confidence intervals (CIs). Multivariate analysis was performed using Poisson regression, accounting for sample weights from the complex survey design. Of 102,302 valid responses, 2333 students reported experiencing racial discrimination, corresponding to a prevalence of 2.58% (95% CI: 2.40–2.78). In multivariate analysis, perceived racial discrimination was associated significantly with being male (PR 1.69; 95% CI: 1.40–2.04), Black (PR 7.39; 95% CI: 5.49–9.96), Brown (PR 2.07; 95% CI: 1.53–2.80) or Indigenous (PR 4.95; 95% CI: 3.32–7.38); working (PR 1.48; 95% CI: 1.19–1.85); having a mother with no schooling (PR 1.74; 95% CI: 1.25–2.42); reporting frequent loneliness (PR 2.17; 95% CI: 1.67–2.81) and expecting to complete only high school (PR 1.50; 95% CI: 1.24–1.83). Results indicate that perceived racial discrimination among Brazilian adolescents is influenced by gender, socioeconomic status and psychosocial factors, highlighting the need for structural interventions to reduce discrimination in schools.